Transforming the matryoshka: Merger of Russian regions. Issue 3 (1st December 2019) - Okunev, Igor Yu.; Oskolkov, Petr V.; Tislenko, Maria I.
Abstract : English abstract: This article assesses the 2000s reforms of the Russian administrative divisions and the implications of the reforms for the institutional structure and related discourse through institutional and discourse analysis. The authors reach the conclusion that the "special status" of the newly formed territorial entities remains undefined, while the representation norm is highly uneven, since the competences of governing bodies in the merged entities lie predominantly in the ethnic and cultural sphere. The reform was not a single and coherent policy measure but rather a number of incoherent initiatives. This can be seen from the presence of different (re)integration models in respective amalgamation cases, different models of a "special status" and a variety of reactions to the reform emanating from the population. Spanish abstract: Este artículo evalúa las reformas del 2000 en las divisiones administrativas rusas y las implicaciones de dichas reformas en la estructura institucional y el discurso relacionado, a través del análisis institucional y del discurso. Los autores llegan a la conclusión de que el "estatus especial" de las entidades territoriales recién formadas permanece indefinido, mientras que las normas de representación son desiguales, ya que las competencias de los órganos rectores en las entidades fusionadas residen predominantemente en la esfera étnica y cultural. La reforma no fue una medida política única y coherente, sino una serie de iniciativas incoherentes. Esto se puede ver por la presencia de diferentes modelos de (re) integración en los respectivos casos de amalgamación, diferentes modelos de un "estatus especial" y una variedad de reacciones a la reforma que emanan de la población. French abstract: Cet article analyse les réformes des divisions administratives russes de l'année 2000 et leurs implications pour la structure et le discours institutionnels, en utilisant les méthodes institutionnelle et discursive. Les auteurs concluent que le « statut spécial » des entités territoriales nouvellement formées reste indéfini, tandis que la norme de représentation demeure très inégale, les compétences des organes directeurs des entités fusionnées étant principalement concentrées dans les domaines ethnique et culturel. La réforme ne constitue pas une mesure politique cohérente, mais un certain nombre d'initiatives incohérentes. La présence de différents modèles de (ré)intégration dans les cas de fusion évoqués, les divers cas de « statut spécial » et la variété des réactions populaires face à cette réforme en témoignent.